(Ignore work below) Pls help solve! Show steps
![Ignore work below Pls help solve Show steps class=](https://us-static.z-dn.net/files/d14/578121ced7be54a8030ddb3032e6d922.png)
Answer:
4[tex]x^{4}[/tex] - 4x³ + 20x² - 20x
Step-by-step explanation:
(g × f)(x) = g(x) × f(x) = (x³ + 5x)(4x - 4)
Each term in the second factor is multiplied by each term in the first factor, that is
x³(4x - 4) + 5x(4x - 4) ← distribute both parenthesis
= 4[tex]x^{4}[/tex] - 4x³ + 20x² - 20x
This can also be done using FOIL, that is
(x³ + 5x)(4x - 4)
= 4[tex]x^{4}[/tex] - 4x³ + 20x² - 20x